Association of Functional Outcome and Post Stroke Depression among Ischemic Stroke Patients after Three Months Onset: A Preliminary Study - Handayani, Fitria; Setyowati, Setyowati; Pudjonarko, Dwi; Sawitri, Dian Ratna; Sakti, Hastaning; Suparyatmo, J.B; Adi, Matius Sakundarno (Jurnal Keperawatan Soedirman, 2019)
Background The Post Stroke Depression (PSD) prevalence of stroke survivor after three months onset was ranged from 17% to 37%. Depression led to fatigue, low quality of life, severe morbidity, and mortality.  Functional Outcome influence depression on stroke survivor.  However, correlation between functional state level and depression among stroke survivor after three months onset has not been established. ObjectiveThis study was aimed to investigate the correlation of executive functional outcome and PSD among stroke survivor after three months onset. MethodThis study was a correlation study. The participants were 44 stroke ischemic patients after three months onset. Participants were recruited in an outpatient unit. PSD was measured using The GRID-Hamilton Rating Scale for Depression 17 (GRID-HAMD 17) and Functional Outcome was measured using Barthel Index (BI). The reliability of GRID-HAMD 17 was .776.  Both instruments were conducted on backward translation in to bahasa. Data was examined using simple linier regression analyses.  The ethical approval was obtained from the Ethical Research Committee of the Medical Faculty Diponegoro University and Tugurejo Semarang Hospital. ResultsThe presence of PSD were 56.82. The median of HAMD-GRID-17 was 10.38 ± 7.58, and Barthel Index was 69.56 ± 21.69.  The Barthel Index showed positive correlation with HAMD-GRID-17 (?= -.41 ?=.006). The Functional Outcome determined PSD as much as 16.8 %. ConclusionModerate association demonstrated the correlation between Functional Outcome and PSD. Nursing intervention should consider these two variables for an optimum quality of life among stroke survivors.